Pengukuran Kepuasan Pelayanan Biro Sumber Daya Manusia: Pengukuran Kepuasan Layanan Departemen Sumber Daya Manusia - Jeziano Rizkita Boyas; Aufa Izzudin Baihaqi; Muh. Aris Izzudin (Universitas Nahdlatul Ulama Sidoarjo, 2023)
The purpose of this study was to evaluate the level of employee satisfaction with the services provided by the Human Resources Bureau at one of the universities in Greater Surabaya. The survey method was used to collect data from 54 employees at a university in Greater Surabaya. The data obtained was analyzed using descriptive quantitative to determine the level of employee satisfaction with the services of the Human Resources Bureau at one of the universities in Greater Surabaya. The results of the study show that most employees are satisfied with the services provided by the Human Resources Bureau with an average score of 4.22 out of a scale of 5. However, there are several aspects that need to be improved, such as response speed and service quality. In conclusion, the services provided by the Human Resources Bureau at a university in Greater Surabaya have met the expectations of employees in general, but need improvement in certain aspects.